Enhancing Academic Excellence in a Malaysian Secondary School Via The Development of Strategic Study Orientation Skills Devices - Mohd Ghani, Awang; Suriya Kumar, Sinnadurai; Muhammad Nubli, Abdul Wahab (IJSCH, UK, 2014)
The purpose of this research is to develop study orientation strategic tools towards achieving academic excellence among form five science stream students of Sg. Isap Secondary School. The measurement of study orientation skills is done by innovating a website based on a survey of study habits and attitudes questionnaire (SSHA) The students’ study orientation skills are analyzed and sorted into; higher achievers, normal achievers and lower achievers. 23 respondents were selected by simple random The research uses Quasi-experimental design with a pre-test and post-test by comparing both group samples. The finding has shown that the study orientation skills (SOS) website was able to measure SOS effectively among the group respondents. There is a significant difference in SOS between pre-test and post test scores of the respondents and also shows that there is a correlation between SOS and GPA scores in pre-test and post-test within and between each group. Keywords: study orientation, study habits, attitude academic excellence,strategic tools,academic performance